Uji Aktivitas Ekstrak Etanol Buah Dewandaru (Eugenia uniflora L.) terhadap Penurunan Kadar Glukosa Darah pada Mencit (Mus musculus) yang Diinduksi Aloksan - Nggaba, Ellenoire Rambu Kabeba Hammu; Santoso, Puguh; Udayani, Ni Nyoman Wahyu (Usadha, 2024)
Diabetes mellitus is a metabolic disorder characterized by a high increase in blood glucose that exceeds normal limits. Treatment based on natural ingredients can be an alternative to the treatment of diabetes. Plants that can be used are Dewandaru Fruit. This study used an experimental method (Pretest-Posttest Control Group Design) to determine whether there is a difference in blood glucose levels in alloxan-induced mice before and after administration of ethanol extract of dewadaru fruit. The extract was made by maceration method. Experimental animals were divided into 4 groups, each containing 6 mice. Group 1 (negative control) received alloxan, group 2 (positive control) received 5mg glibenclamide, group 3 received 100mg/kgBW extract, and group 4 received 200mg/kgBW extract. Alloxan-induced mice were subcutaneously measured 3 days after (pretest) and 14 days after treatment (posttest) using a glucometer. Data were analyzed using SPSS 26 with the Shapiro-Wilk normality test and pretest and posttest comparison test using Paired T-Test analysis. Based on the results of statistical tests, the study concluded that there was a significant difference in the decrease in blood glucose levels in alloxan-induced mice (Mus musculus) after being given the ethanol extract of Dewadaru fruit at doses of 100 mg/kgBW and 200 mg/kgBW. Keywords: Antidiabetic; Flavonoid; Blood Sugar Levels; Dewandaru  (Eugenia uniflora L.)